ANALISIS RASIO PROFITABILITAS DAN LIKUIDITAS UNTUK MENILAI KINERJA KEUANGAN PT. AIRASIA INDONESIA TBK TAHUN 2018 - 2019 - MARKUS DODDY SIMANJUNTAK (JURNAL ILMIAH MAKSITEK, 2021)
The purpose of this research was to calculate and analyze the ratio of profitability and liquidity to financial performance in PT.Airasia Indonesia Tbk in 2018-2019. In the period 2018, the current ratio was 26.09 %, the Debt to Equity Ratio was8,237.55% and the ROE ratio was 213.71% ,From the data it can be known that the current ratio of the companyexperienced a very sharp decrease, so that the liquidity condition of the company is very far from liquid or in other words, thecompany's current assets are not able to cover its current debt. In 2019, the current ratio was 16.3%, the Debt to EquityRatio was 454.67% and the ROE ratio was 7.18%. Based on the data, it can be known that the company's current ratiodecreased from 2018. This means that the company's liquidity condition is worse than the previous year. Similarly, the Debtto Equity Ratio, decreased from the previous year. This has an effect on roe ratio which also experienced a very sharpdecline.